Transformative impact of ai on multicultural education: A qualitative thematic analysis - Dwi, Mariyono; Nur Alif Hd, Akmal (Edelweiss Applied Science and Technology, 2024)
This research explores the transformative impact of Artificial Intelligence (AI) on multicultural education through a qualitative thematic analysis of existing literature. The study aims to understand how AI technologies can be harnessed to foster inclusive and culturally responsive educational environments. By analyzing various case studies and scholarly articles, this paper identifies key themes such as personalized learning, cultural sensitivity, ethical concerns, and the digital divide. The findings highlight AI’s potential to revolutionize educational practices, promote inclusivity, and prepare students for a globalized world, while also addressing significant challenges and proposing solutions to mitigate them.